GRP-145 Potentially Inappropriate Prescribing in Elderly Fallers: A Review of Current Practise and the Impact of Pharmacist-Led Medicines Reviews. (12th March 2013) - O'Sullivan, D; Carroll, J; Meegan, C
Abstract : Background: Falls in the elderly represent a significant health burden in Ireland and internationally. Falls are consistently the most frequently reported patient incident in the MMU Hospital. Polypharmacy and inappropriate prescribing are considered important extrinsic risk factors for falling. Section H of the Screening Tool of Older Persons' Potentially Inappropriate Prescriptions (STOPP) criteria relates to medicines known to adversely affect fallers. Purpose: To explore the current level of medicines review afforded to elderly fallers. To determine if use of the STOPP criteria & subsequent pharmacist intervention result in a greater reduction in the number of prescriptions for, & the number of patients receiving, ≥1 potentially inappropriate medicines (PIMs), compared to the current standard of care. To develop prescribing guidelines for inclusion in a future falls prevention policy for the hospital. Materials and Methods: A STOPP-based research protocol for the identification of PIMs in elderly fallers was developed and piloted. A programme of usual care versus pharmacist intervention was undertaken. In the intervention study the investigator alerted medical teams to PIM(s) through communication in patients' medical notes. Ward pharmacists reviewed patients' drug charts after the investigator's review, & recorded changes to identified PIMs. The investigator participated in a falls working group set up to develop and implement a policy on the prevention of falls in MMUH. Results: Pharmacist intervention resulted in reductions in both the number of patients prescribed ≥1 PIM, & prescriptions for PIMs; however, these results failed to reach statistical significance (P = 0.08 & 0.074, respectively). Patients prescribed ≥1 PIM were taking 3 more regular medicines than those who were not (p < 0.001). The MMUH Falls Working Group developed a policy on falls prevention. The STOPP criteria were used to formulate the relevant sections relating to medicines & falls. Conclusions: Pharmacist intervention may have a positive impact on rates of potentially inappropriate prescribing in elderly patients who fall during admission. However, further research is needed. No conflict of interest.